Industrial software engineering developing software systems. - Lanman, Jeremy T. (Software engineering notes.)
Software Engineering is an incredibly complex interdisciplinary subject that requires intense problem solving and communication skills. It is an art and a science which requires an open mind and adaptation to various domains. . . in essence, a software engineer must think outside of the box! I started my path in software engineering with the undergraduate computer science program at Butler University. There I learned the common fundamentals of computer science through studying algorithms and data structures, theory of computing, databases, and of course discrete mathematics. In addition to a traditional computer science program, a software engineering curriculum was introduced. Although, nearing graduation, I decided to take a couple of these software classes, and afterwards it was clear to me that my passion was to develop software systems. I decided to learn more and enrolled into a graduate program in software engineering at Embry-Riddle Aeronautical University. At ERAU, I had specific courses in each area of the software engineering development lifecycle, and collaborative corporate internships to apply my knowledge. My most profound internship was with the aerospace defense contractor, Lockheed Martin Corporation. It was there where I truly learned how to be an "Industrial Software Engineer".